Dysfunction in the Interaction of Information Between and Within the Bilateral Primary Sensory Cortex - Xing, Xiang-Xin; Ma, Zhen-Zhen; Wu, Jia-Jia; Ma, Jie; Duan, Yu-Jie; Hua, Xu-Yun; Zheng, Mou-Xiong; Xu, Jian-Guang (Frontiers in Aging Neuroscience, 2022)
Abstract: Background: Inter- and intrahemispheric long-range synchronization and information communication are crucial features of functional integration between the bilateral hemispheres. Previous studies have demonstrated that disrupted functional connectivity exists in the bilateral hemispheres of carpal tunnel syndrome (CTS) patients, but they did not clearly clarify the phenomenon of central dysfunctional connectivity. The current study aimed to further investigate the potential mechanism of the weakened connectivity of S1 based on a precise template. Methods: CTS patients (N=53) and healthy control subjects (N=23) participated and underwent resting-state functional magnetic resonance imaging scanning. We used functional connectivity (FC) to investigate the statistical dependency of the whole brain, effective connectivity (EC) to analyze time-dependent effects, and voxel-mirrored homotopic connectivity (VMHC) to examine the coordination of functional connectivity, all of which were adopted to explore the change in interhemispheric and intrahemispheric S1. Results: Compared to the healthy controls, we found significantly decreased strength of the two connectivities in the interhemispheric S1hand, and results of EC and VMHC were basically consistent with FC in the CTS. The EC revealed that the information output from the dominant hemisphere to the contralateral hemisphere was weakened. Conclusions: The study found that maladjusted connections between and within the bilateral S1 revealed by these methods are present in CTS patients. The dominant hemisphere with deafferentation weakens its effect on the contralateral hemisphere. The disturbance in the bilateral S1 provides reliable evidence to understand the neuropathophysiological mechanisms of decreased functional integration in the brains of CTS patients.